Implementation Public Relations Performance of The Bogor City Legislative Council Secretariat in Improving Communication Strategies Digital Insta-gram Account @Setwankotabogor - Denariansyah, Azqia; Bachtiar, Willy (IJESS International Journal of Education and Social Science, 2025)
In the era of digitalization and bureaucratic reform, demands for transparency, accountability and openness of public information are getting higher. This research aims to analyze the implementation of the Public Relations performance of the Bogor City DPRD Secretariat in managing digital communication strategies through the @setwankotabogor Instagram account, as well as identifying challenges faced and steps taken to improve the effectiveness of public communication. The research method used is descriptive qualitative with an observation approach, in-depth interviews, and literature studies. The results showed that the Public Relations of the Bogor City DPRD actively utilizes Instagram as the main communication media with a focus on disclosing information on official activities and building a positive image of the institution. However, significant challenges faced include limited human resources, digital work tools, and content creativity. To address these challenges, public relations implemented a strategy of adaptation to digital trends, regular content evaluation, intensive internal coordination, and utilization of big moments to increase information reach. This research confirms the important role of government public relations in building two-way communication with the public through an adaptive and structured digital strategy.